Produksi dan Pemasaran Melalui Media Digital Sebagai Inovasi Baru Pengembangan Produk Sarigono - Jaya, Adi; Prastiawan, Hendri; Shepiani, Nuril; Anjani, Divanti Sylvia; Putri, Safira Nabila; Utama, Andean Ilham Nuralivian; Fadhillah, Azzara Nur; Anam, Muhammad Rizqy; Lesmana, Dhia Adi; Kusnendar, Muhamad (Universitas Muhammadiyah Yogyakarta, 2024)
Since the emergence of social media platforms, people's behavior tends to change and many turn into social media users. This is then used as a variety of modifications by many economic actors, such as developing their sales stalls from offline to online which tend to be easier to see and buy by users around the world. Many marketing strategies have emerged, ranging from advertising to paying adsense to improve their brand branding. Sarigono Hamlet, located in the corner of Yogyakarta Special Region, has many hidden potentials. One of these potentials is the Talas Chips product produced by the Honey Lestari Women Farmers Group (KWT). This product needs to be developed and marketed more widely. KKN 137 came up with an initiative to transform marketing from direct methods to social media utilization. By using Instagram and Shopee as marketing platforms, it is expected to increase the reach and sales of Talas Chips products. In addition, KKN UMY 137 also implements programs that focus on improving the economy and politics in Sarigono Hamlet with the aim of improving the welfare of the Sarigono community.